Exposure to Low-Dose Ionizing Radiation From Cardiac Procedures and Malignancy Risk in Adults With Congenital Heart Disease. Issue 13 (27th March 2018) - Cohen, Sarah; Liu, Aihua; Gurvitz, Michelle; Guo, Liming; Therrien, Judith; Laprise, Claudie; Kaufman, Jay S.; Abrahamowicz, Michal; Marelli, Ariane J.
Abstract : Background: Adults with congenital heart disease (CHD) are exposed to increasing amounts of low-dose ionizing radiation (LDIR) from cardiac procedures. Cancer prevalence in this population is higher than in the general population. This study estimates the association between LDIR exposure from cardiac procedures and incident cancer in adult patients with CHD. Methods: The study population derived from the Quebec Congenital Heart Disease Database. We measured cumulative numbers of LDIR-related cardiac procedures for each patient until 1 year before the time of cancer diagnosis or administrative censoring. To assess the association between LDIR exposure and cancer risk, we conducted a nested case-control study and matched cancer cases with controls on sex, CHD severity, birth year, and age. Results: The study included 24 833 adult patients with CHD aged 18 to 64 years from 1995 to 2009. In >250 791 person-years of follow-up, 602 cancer cases were observed (median age, 55.4 years). The cumulative incidence of cancer estimated up to 64 years of age was 15.3% (95% confidence interval [CI], 14.2–16.5). Cases had more LDIR-related cardiac procedures than controls (1410 versus 921 per 1000 adult patients with CHD, P <0.0001). Cumulative LDIR exposure was independently associated with cancer (odds ratio [OR], 1.08 per procedure; 95% CI, 1.04–1.13). Similar results were obtained by using dose estimates for LDIR exposure (OR, 1.10 per 10 mSv; 95% CI, 1.05–1.15) with a possible dose-related response. The effect measure was in the same direction, and the association was persistent for exposure from ≥6 procedures in all sensitivity analyses: after excluding most smoking-related cancer cases (OR, 1.10 per procedure; 95% CI, 1.05–1.16 and OR when exposure from ≥6 procedures, 3.08; 95% CI, 1.77–5.37), and after applying a 3-year lag period (OR, 1.09 per procedure; 95% CI, 1.03–1.14 and OR when exposure from ≥6 procedures: 2.58; 95% CI, 1.43–4.69). Conclusions: To our knowledge, this is the first large population-based study to analyze and document the association between LDIR-related cardiac procedures and incident cancer in the population of adults with CHD. Confirmations of these findings by prospective studies are needed to reinforce policy recommendations for radiation surveillance in patients with CHD where no regulation currently exists. Physicians ordering and performing cardiac imaging should ensure that exposure is as low as reasonably achievable without sacrificing quality of care. Abstract : Supplemental Digital Content is available in the text.